RELATIONSHIP BETWEEN LEVELS OF KNOWLEDGE AND ATTITUDE WITH DRUG COMPLIANCE AMONG PATIENT WITH HYPERTENSION - Dini Justian; Tiara Dwi Rahma (PHSAJ - Public Health Sebelas April Journal, 2022)
Hypertension or high blood pressure itself can be described as the force of circulating blood against the walls of the body's arteries which are the main blood vessels. The amount of pressure that occurs depends on the resistance of the blood vessels and how intense the heart is to work. To determine the relationship between the level of knowledge and attitudes with medication adherence in patients with hypertension at the Paseh Health Center in 2022. This type of research used a quantitative study with a cross sectional design with a sample of 100 people using accidental sampling. This study shows that knowledge of hypertension sufferers is in the good category, namely 60.0%, the attitude of hypertension sufferers is in the good category, namely 49.0% and compliance with hypertension sufferers is in the obedient category, namely 50.0%. By using the Chi square statistical test where the degree of confidence used is 95% and = 0.05, the p value for knowledge is 0.000 and the P value for attitude is 0.008. So that the null hypothesis is rejected or in other words it is statistically proven. Conclusions and suggestions: the relationship between knowledge and attitudes with medication adherence. Suggestions in this study are expected health workers to continue to carry out outreach activities regarding adherence to taking medication in patients with hypertension.